Modified Montmorillonite Improved Growth Performance of Broilers by Modulating Intestinal Microbiota and Enhancing Intestinal Barriers, Anti-Inflammatory Response, and Antioxidative Capacity - Qi Wang; Xiaoli Zhan; Baikui Wang; Fei Wang; Yuanhao Zhou; Shujie Xu; Xiang Li; Li Tang; Qian Jin; Weifen Li; Li Gong; Aikun Fu (MDPI AG, 2022)
This study aims to explore the effects of modified montmorillonite (MMT, copper loading) on the growth performance, gut microbiota, intestinal barrier, antioxidative capacity and immune function of broilers. Yellow-feathered broilers were randomly divided into control (CTR), modified montmorillonite (MMT), and antibiotic (ANTI) groups. Results revealed that MMT supplementation increased the BW and ADG and decreased the F/R during the 63-day experiment period. 16S rRNA sequencing showed that MMT modulated the cecal microbiota composition of broilers by increasing the relative abundance of two phyla (Firmicutes and Bacteroidetes) and two genera (Bacteroides and Faecalibacterium) and decreasing the abundance of genus Olsenella. MMT also improved the intestinal epithelial barrier indicated by the up-regulated mRNA expression of claudin-1, occludin, and ZO-1 and the increased length of microvilli in jejunum and the decreased levels of DAO and D-LA in serum. In addition, MMT enhanced the immune function indicated by the increased levels of immunoglobulins, the decreased levels of MPO and NO, the down-regulated mRNA expression of IL-1β, IL-6, and TNF-α, and the up-regulated mRNA expression of IL-4 and IL-10. Moreover, MMT down-regulated the expression of jejunal TLRs/MAPK/NF-κB signaling pathway-related genes (TLR2, TLR4, Myd88, TRAF6, NF-κB, and iNOS) and related proteins (TRAF6, p38, ERK, NF-κB, and iNOS). In addition, MMT increased the antioxidant enzyme activities and the expression of Nrf2/HO-1 signaling pathway-related genes and thereby decreased the apoptosis-related genes expression. Spearman's correlation analysis revealed that Bacteroides, Faecalibacterium, and Olsenella were related to the inflammatory index (MPO and NO), oxidative stress (T-AOC, T-SOD, and CAT) and intestinal integrity (D-LA and DAO). Taken together, MMT supplementation improved the growth performance of broilers by modulating intestinal microbiota, enhancing the intestinal barrier function, and improving inflammatory response, which might be mediated by inhibiting the TLRs/MAPK/NF-κB signaling pathway, and antioxidative capacity mediated by the Nrf2/HO-1 signaling pathway.